Pengaruh Penerapan Anggaran Berbasis Kinerja, Kejelasan Sasaran Anggaran Dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja Di Kantor Wilayah Kementerian Hukum Dan HAM Riau - Arini; Simamora, Sartika; Kamilah, Faizah (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2024)
This study aims to test and determine the Influence of Performance-Based Budget Implementation, Clarity of Budget Targets and Reporting System on Performance Accountability at the Riau Ministry of Law and Human Rights Regional Office. The population in this study was 61 people. Then for sampling, the author used a saturated sampling technique where the entire population was sampled, namely Employees/Officials in the finance section and the General Section at the Correctional and Immigration Technical Implementation Unit and the Riau Ministry of Law and Human Rights Regional Office. This type of research is Quantitative. Data collection techniques used in this study are Questionnaires and Documentation. The research method used in this study is multiple linear regression, with the help of SPSS 26. The results of this study indicate that the Implementation of Performance-Based Budgeting, Clarity of Budget Targets and Reporting System together have an effect on Performance Accountability at the Riau Ministry of Law and Human Rights Regional Office. As shown from the results of the t-test, namely partially Performance-Based Budget has an effect on Performance Accountability with a t-value of 2.709> 2.002 and a significant value of 0.009 <0.05. Then Clarity of Budget Targets partially has an effect on Performance Accountability with a t-value of 6.755> 2.002 and a significant value of 0.00 <0.05. Then the Reporting System partially has an effect on Performance Accountability with a t-value of 2.889> 2.002 and a significant value of 0.005 <0.05. Then from the results of the F Test, namely f count 91.297> f table value 2.77 and with a significance value of 0.000 <0.05. And has an R Square value of 81.9%, while the remaining 18.1% is influenced by other variables not included in this regression model.